Global initiatives in physical education and sport development - Tsybanyuk, Oleksandra; Dariichuk, Serhii; Pobocha, Tetiana; Moseichuk, Yurii (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to analyse the impact of international projects in the field of physical culture and sports on the development of this industry at the global and national levels. The research methodology included a comparative analysis of the effectiveness of implemented projects, empirical research of results, and statistical methods to assess their impact on socio-economic indicators. The study shows that international projects have attracted young people to sports, increased the number of sports initiatives, and expanded best practices in the field of physical education; for example, with the participation of international organisations, the level of physical activity increased by 15-20% in countries that have implemented relevant programmes. At the same time, these projects have contributed to create an inclusive environment for people with disabilities and stimulated socialisation through sport. The practical significance of the results obtained is to formulate recommendations for developing and implementing international projects in the field of physical culture. This contributes to the further development of international cooperation by promoting a healthy lifestyle and improving the population’s quality of life.